Comparison of short-term results in THA patients with SuperPath® and the conventional approach for dysplastic OA of the hip - Hagio, Keisuke; Aikawa, Kazuhisa; Akiyama, Keisuke (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Although there have been many reports of comparative studies between SuperPath® and other approaches for THA with primary OA of the hip, there have been no reports of comparative studies of THA for secondary OA. The purpose of this study is to compare clinical outcomes and lower extremity recovery between THA of SuperPath® approach (Group S) and that of conventional posterior approach (Group C). Methods: Both 30 patients (Group S) and 36 patients (Group C) were investigated for clinical scores and recovery of lower limb function. Results: JOA scores showed no significant difference in preoperatively (group C: 46.5±9.2, Group S: 48.4±8.2, p=0.30), but at discharge (Group C: 76.8±4.3, Group S: 86.7±5.1, p<0.01) and postoperative 2 months (Group C: 85.0±3.5, Group S: 91.5±7.2, p<0.01) they were significantly improved in group S over group C. The mean length of stay was 16.3±4.9 days for group S, which was significantly shorter than of 25.5±4.6 days in group C (p<0.01). In terms of recovery of lower limb function, a mean time from postoperative to walking 50-meters with a cane was 3.2±2.3 days in group S, significantly shorter than that of 13.8±5.1 days in group C (p<0.01). The mean time to achieve ascend and descend of stairs using a handrail was 3.8±1.4 days in group S, significantly shorter than that of 12.8±5.1 days in group C (p<0.01). Conclusions: Clinical outcomes were good in both groups with mild dysplasia, but lower extremity function recovered significantly faster in group S than in group C.